Renal Function in Children with β-Thalassemia Major Treated with Iron Chelating Agent - Olga Rasiyanti Siregar; Rosmayanti Syafriani Siregar; Bidasari Lubis (The Indonesian Biomedical Journal, 2020)
BACKGROUND: Thalassemia is a disorder of inherited blood and inticated by the abnormal hemoglobin. Transfusion and iron chelation are part of thalassemia management. Iron chelating agent reduces complications due to the excess iron as a result of repeated transfusions, hence, increasing the survival rate. However, prolonged intake of iron chelating agent may increase the risk of renal function impairment. To date, evaluation of renal function in children with β-thalassemia in Medan has never been reported. The objective of this study was to evaluate renal function and other factors in children with β-thalassemia.METHODS: Fourty-five children with β-thalassemia was recruited in this study. Renal function, represented by estimated glomerular filtration rate (eGFR)and serum ferritin levels were examined. The measurement of eGFR was using Schwartz method.RESULTS: Decreased eGFR observed in some the children (2 patients) with β-thalassemia major treated with iron chelating agent. None of the factors examined had association with serum creatinine level. Children's age and duration of iron chelating agent intake had positive correlation with their eGFR (r=0.506, p<0.001 and r=0.518, p<0.001, respectively). However, serum ferritin levels was not a predictor for renal function impairment.CONCLUSION: Most of children with β-thalassemia major treated with iron chelating agent have normal renal function, nevertheless, decreased renal function is observed in few children. Highlighted, renal function examinations should be performed routinely as iron chelating agent administration is a long-term therapy in children with β-thalassemia major.KEYWORDS: β-thalassemia major, renal function, serum ferritin levels, iron chelating agent